(untitled) (Journal of Economic Research & Business Administration, 2016)
The process of globalization of the world economy is growing every day, and every civilized society aspires to, to find its rightful place in this race fighting. The annual growth of Kazakhstan’s economy occurs mainly due to crude oil and petroleum products and other natural resources. The issue of increasing the updated design for Kazakhstan became one of the most urgent measures to be undertaken in the future. In accordance with this, the President of the Republic of Kazakhstan Nursultan Nazarbayev, considering our country with great potential, competitive, comprehensive development, as well as fully compliant with the complex developed in the framework of the 30 countries as a member of the WTO will lead to what will be increased ways to increase the competitiveness of products manufactured by companies in the country, as today it is an urgent issue.